$\large \log_{b}{(m)} = \dfrac{1}{\log_{m}{(b)}}$

The quantity and base in a logarithmic term can be switched by changing the base in reciprocal form. It is called as base switch rule of logarithms and it is used as a formula in logarithmic mathematics.

The change of base formula for logarithm in reciprocal form is derived in logarithmic mathematics by using the rules of exponents and mathematical relation between exponents and logarithms.

$\log_{b}{m}$ and $\log_{d}{b}$ are two logarithmic terms and it is assumed that the values of them are $x$ and $y$ respectively.

$\log_{b}{m} = x$ and $\log_{d}{b} = y$

The equations in logarithmic form can be written in exponential form by the mathematical relationship between exponents and logarithms.

$(1) \,\,\,$ $\log_{b}{m} = x \,\Leftrightarrow\, m = b^{\displaystyle x}$

$(2) \,\,\,$ $\log_{d}{b} \,\,\, = y \,\Leftrightarrow\, b = d^{\displaystyle y}$

The change of base formula can be written in mathematical form by this data.

$\log_{b}{m} = \dfrac{\log_{d}{m}}{\log_{d}{b}}$

Take $d = m$ and eliminate $d$ by $m$ in the change of base formula.

$\implies$ $\log_{b}{m} = \dfrac{\log_{m}{m}}{\log_{m}{b}}$

Mathematically, the logarithm of a quantity (equals to base) is always one as per log base rule. Therefore, $\log_{m}{m} = 1$ and write the change of base formula.

$\,\,\, \therefore \,\,\,\,\,\,$ $\log_{b}{m} = \dfrac{1}{\log_{m}{b}}$

Latest Math Topics

Latest Math Problems

A best free mathematics education website for students, teachers and researchers.

Learn each topic of the mathematics easily with understandable proofs and visual animation graphics.

Learn how to solve the maths problems in different methods with understandable steps.

Copyright © 2012 - 2021 Math Doubts, All Rights Reserved